THE PRINCIPAL'S OF LEADERSHIP STYLE ON TEACHERS PERFORMANCE - Suroso, Budi; Anggoro, Subuh (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
ABSTRACT Principal leadership and teacher performance are inseparable things . Improving the quality of education is determined by the human resources involved in the education process. There are many factors that can improve teacher work performance. One of them is the leadership of the principal. The leadership style of the principal is very influential on performance. teacher This study aims to analyze the effect of the principal's competence on ork motivation and teacher performance. This research is a qualitative study using a survey. Data collection was carried out using a questionnaire and analyzed using with the samples studied were principals and teachers. From the results of research in the field it is concluded that in general the principal's performance is fairly good, and this has an impact on the good performance of teachers as well.